Chinese American Identity in the Novels of Amy Tan - Gordan Matas (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
This paper analyzes the role of ethnicity and identity in the works of Chinese American author Amy Tan. Her first two novels, The Joy Luck Club and The Kitchen God’s Wife, are discussed from the perspective of ethnic, multicultural, and cultural studies. Tan’s works provide detailed and sincere insight into the lives of first- and second-generation Chinese immigrants in the United States. Tan’s novels provide a lot of information on ethnicity and identity, as well as on the Chinese American community in general. This work aims to show that immigrants do not necessarily lose their ethnic identity while living in the United States. Moreover, they frequently strive to preserve their original culture, sometimes adapting it to their new environment. They want to retain their own cultural and ethnic heritage as well as their personal identity, while assimilating into the new country and new circumstances. By employing comparative and contrastive analysis of selected Tan novels, this paper will show how Tan, in a unique way, negotiated the relationship between ethnicity and identity in her novels. Tan's rendering of ethnic identity has not been addressed in this way previously, and this study contributes to a more thorough understanding of Tan's work.